1963
DOI: 10.1002/path.1700850214
|View full text |Cite
|
Sign up to set email alerts
|

The permeability to plasma proteins of the peritoneal blood vessels of the mouse, and the effect of substances that alter permeability

Abstract: PERITONms is associated with the accumulation of plasma protein in the peritoneal cavity, and a study is being made of the significance of this protein in the defence against bacterial infection. The accumulation of plasma protein in the peritoneal cavity can be measured by a method involving labelling the circulating plasma protein with Evans blue: this method for studying the permeability of the peritoneal vascular bed has the advantage that it can be used for investigating conditions ranging from approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1964
1964
2001
2001

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Peritonitis is associated with the accumulation of plasma proteins in the abdominal cavity [1,2], Losses of proteins in the dialysate effluent of patients treated by means of peritoneal dialysis are substantially increased during episodes of peritonitis [3][4][5][6][7][8][9][10][11][12]. This increased peri toneal permeability to anionic plasma proteins, the path ophysiology of which has not yet been clearly elucidated, occurs without parallel changes on peritoneal clearances of small solutes like urea (uncharged) and creatinine (cationic).…”
Section: Introductionmentioning
confidence: 99%
“…Peritonitis is associated with the accumulation of plasma proteins in the abdominal cavity [1,2], Losses of proteins in the dialysate effluent of patients treated by means of peritoneal dialysis are substantially increased during episodes of peritonitis [3][4][5][6][7][8][9][10][11][12]. This increased peri toneal permeability to anionic plasma proteins, the path ophysiology of which has not yet been clearly elucidated, occurs without parallel changes on peritoneal clearances of small solutes like urea (uncharged) and creatinine (cationic).…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with the hypothesis of a central mechanism as the major causative factor for EOCz induction of antinociceptive effects. On the other hand, contortions induced by intraperitoneal injections of acetic acid are said to originate from the pain of inflammation mediated by prostaglandins (15)(16)(17). Experiments not included in the results of this study showed that 300 mg/kg EOCz did not alter mouse motor performance in the rotorod test.…”
mentioning
confidence: 65%
“…This is made more probable by the fact that phenylacetate and gentisate, non-antiinflammatory analogues of indomethacin and salicylate respectively (Northover, 1963;1964;Durant, Smith, Spickett & Szarvasi, 1965) (Rajan, 1966;Andrews & Phelps, 1971;Oronsky, Ignarro & Perper, 1973;Weissmann, 1973;Wright & Malawista, 1973;Hawkins, 1974;Ignarro, 1974a;Perper & Oronsky, 1974;Ackerman & Beebe, 1975;Goldstein, 1975;Lewis & Day, 1975;Malawista, 1975;Oronsky & Perper, 1975). As noted previously, stimulus-secretion coupling mechanisms may vary with the nature of the stimulus involved, and consequently may vary in their capability of being inhibited by drugs.…”
Section: Effect Of Other Anti-inflammatory Drugsmentioning
confidence: 92%